Progress in Ultrafast Intense Laser Science VI - Yamanouchi, Kaoru; Gerber, Gustav; Bandrauk, Andre D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The PUILS series delivers up-to-date reviews of progress in Ultrafast Intense Laser Science, a newly emerging interdisciplinary research field spanning atomic and molecular physics, molecular science, and optical science, which has been stimulated by the recent developments in ultrafast laser technologies. Each volume compiles peer-reviewed articles authored by researchers at the forefront of each their own subfields of UILS. Every chapter opens with an overview of the topics to be discussed, so that researchers unfamiliar to the subfield, as well as graduate students, can grasp the importance and attractions of the research topic at hand; these are followed by reports of cutting-edge discoveries. This sixth volume covers a broad range of topics from this interdisciplinary research field, focusing on responses of molecules to ultrashort intense laser pulses, generation and characterization of attosecond pulses and high-order harmonics, and filamentation and laser-plasma interaction.
Laser-Induced Coulomb Explosion Ultrafast Imaging of Molecules -- Quantum Switching of Magnetic Fields by Circularly Polarized Re-Optimized ? Laser Pulses: From One-Electron Atomic Ions to Molecules -- Alignment and Orientation of Hexapole State-Selected Molecules -- Quantum Interference in Ionization of Excited Molecules: X-Ray Emission Control and Dynamic Imaging -- Single Isolated Attosecond Pulses Generation with Double Optical Gating -- Toward the Generation of Isolated Attosecond Pulses in the Water Window -- High Harmonic Generation by Plasmonic Enhancement of Femtosecond Pulse Laser -- High-Order Harmonic Generation from Nanostructured Material Using the Laser-Plasma Method -- Filamentation in Ultrafast Laser Material Processing -- Plasma Electron Kinetics and Distribution Functions in Laser Fields -- Ion Acceleration by Ultra-Intense Lasers: Analysis of Contrast Effects.
Keywords: Physics; Physics; Atomic, Molecular, Optical and Plasma Physics